A review on Life Cycle Assessment, Life Cycle Energy Assessment and Life Cycle Carbon Emissions Assessment on buildings. (1st April 2015) - Chau, C.K.; Leung, T.M.; Ng, W.Y.
Highlights: Three streams of life cycle studies, namely LCA, LCEA and LCCO2 A, were compared. Previous findings from the three streams were reviewed. Cases led to discrepancies of results arising from different types of life cycle studies were discussed. Limitations in using life cycle studies as decision tools for building design were identified. Abstract: This paper provides a review on three streams of life cycle studies that have been frequently applied to evaluate the environmental impacts of building construction with a major focus on whether they can be used for decision making. The three streams are Life Cycle Assessment (LCA), Life Cycle Energy Assessment (LCEA) and Life Cycle Carbon Emissions Assessment (LCCO2 A). They were compared against their evaluation objectives, methodologies, and findings. Although they share similar objectives in evaluating the environmental impacts over the life cycle of building construction, they show some differences in the major focuses of evaluation and methodologies employed. Generally, it has been revealed that quite consistent results can be derived from the three streams with regard to the relative contribution of different phases of life cycle. However, discrepancies occur among the findings obtained from the three streams when different compositions of fuel mixes are used in power generation, or when the overall impacts are not contributed mostly by greenhouse gases emissions. The use of different functional units in different studies also makes it difficult to compare results with benchmarks or results from previous studies. Besides, there are drawbacks in boundary scoping, methodology framework, data inventory and practices which impair their usefulness as a decision making support tool for sustainable building designs.